Pengaruh Asupan Berbagai Jenis Biji-bijian Terhadap Peningkatan Kadar Asam Urat pada Tikus Putih Jantan (Rattus norvegicus) - Dhanang Puspita; Rosiana Eva Rayanti; Yohana Ikka Maylani; Theresia Pratiwi Elingsetyo Sanubari (Seminar Nasional Teknik Kimia Kejuangan, 2017)
Grains known as foods that contain purine. The existence of purines can cause gout patients/ hyperuricemiaincreased levels of uric acid in the blood. High levels of uric acid cause gout arthritis. This study aims todetermine the increase in uric acid levels in male rats (Rattus norvegicus) by the intake of various types ofgrain. Male rats per group were given intake melinjo (Gnemon gnetum), soy (Glycine max), white rice(Oryza sativa), peanuts (Arachis hypogaea), red beans (Phaseolus vulgaris), green beans (Vigna radiata),and BR1 (as control). Long treatment for 15 days. Calculation of uric acid levels in male rats at the start ofthe day to 0, 5, 10, and 15. The measurement results showed that rats with intake a diet melinjo seeds haveelevated levels of uric acid highest is 20 mg/dl and the lowest is peanuts (7,2 mg/dl), while control is 4,2mg/dl. The amount of uric acid content in rats with grain intake showed a high purine content. This studyconcluded that contribute grain in elevated uric acid levels are highest is melinjo, rice, green beans,soybeans, red beans, and peanuts.